Implementasi Peraturan Daerah (PERDA) Nomor 4 Tahun 2014 tentang Perlindungan dan Pemberdayaan Petani / Pembudidaya Nelayan di Kabupaten Sidoarjo : Studi Kasus di Desa Gisik Cemandi-Kecamatan Sedati Kabupaten Sidoarjo-Provinsi Jawa Timur - Marcel Mochammad Reza Ardito; Radjikan Radjikan; Muhammad Roisul Basyar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the implementation of Regional Regulation Number 4 of 2014 concerning the Protection and Empowerment of Farmers and Fish Farmers in Sidoarjo Regency. Focusing on Gisik Cemandi Village as the case study, this research employs a qualitative descriptive approach with Grindle’s policy implementation theory as the main analytical framework. The findings reveal that while various programs such as skill training, fuel subsidies, fishing equipment aid, and institutional strengthening have been carried out, there are still obstacles in equitable distribution, budget constraints, and continuity of the programs. Nevertheless, strong inter-agency coordination, responsiveness of the implementers, and active participation from the fishermen community contributed positively to the overall implementation. This study underscores the importance of aligning public policy with community needs to achieve sustainable development in coastal areas.